Microstructure, Phase Composition, and Mechanical Properties of Intermetallic Ni-Al-Cr Material Produced by Dual-Wire Electron-Beam Additive Manufacturing - Elena Astafurova; Kseniya Reunova; Elena Zagibalova; Denis Astapov; Sergey Astafurov; Evgenii Kolubaev (Metals, 2024)
Electron-beam additive manufacturing is one of the most promising methods for creating complex metal parts and structures. Additive manufacturing has already gained wide acceptance in the creation of various constructions from aluminum, copper, titanium, and their alloys as well as different classes of steels and other metallic materials. However, there are still many challenges associated with the additive manufacturing and post-production processing of intermetallic alloys. Thus, it is currently an urgent task for research. In this work, heat-resistant intermetallic alloys based on nickel, aluminum, and chromium were produced by dual-wire electron-beam additive manufacturing using commercial NiCr and Al wires. The microstructure, phase composition, and microhardness of the intermetallic billets are strongly dependent on the ratio of NiCr and Al wires, which have been fed during the additive growth of the material (NiCr:Al = 3:1 and NiCr:Al = 1:3). A metal-matrix composite material (Al3Ni-based intermetallide in Al-based matrix) was fabricated using the NiCr:Al = 1:3 ratio of the wires during the deposition. In tension, it fractures in a brittle manner before the plastic deformation starts, and it possesses a high microhardness of 6–10 GPa with a high dispersion of the value (the mean value is 8.7 GPa). This is associated with the complex phase composition of the material and the high fraction of a brittle Al3Ni intermetallic phase. In the material, obtained with the ratio NiCr:Al = 3:1, the ordered Ni3Al(Cr) and disordered Ni3Cr(Al) intermetallides are the dominating phases. Its microhardness turned out to be lower (4.1 GPa) than that in Al + Al3Ni-based composite, but intermetallic Ni3Al-based alloy demonstrates good mechanical properties in a high-temperature deformation regime (650 MPa, more than 10% elongation at 873 K). Microstructural studies, analysis of phase composition, and tensile mechanical properties of additively produced intermetallic materials show the perspective of dual-wire electron-beam additive manufacturing for producing intermetallic compounds for high-temperature applications.